Determination of Selected Cathinones in Blood by Solid-Phase Extraction and GC–MS. Issue 3 (19th June 2020) - Antunes, Mónica; Sequeira, Margarida; de Caires Pereira, Mariana; Caldeira, Maria João; Santos, Susana; Franco, João; Barroso, Mário; Gaspar, Helena
Abstract: The emergence of potentially dangerous new psychoactive substances (NPS) is challenging for forensic laboratories, as well as the ability to develop and validate methods for a rapid and unambiguous monitoring of these compounds. Thereupon, the aim of this work was to establish a methodology for the identification and quantification of four synthetic cathinones already seized in Portugal [4-chloroethcathinone (4-CEC), α-pyrrolidinovalerophenone (α-PVP), 4-chloro-pyrrolidinovalerophenone (4-Cl-PVP) and methylenedioxypyrovalerone (MDPV)] in whole blood samples, using gas chromatography coupled to mass spectrometry (GC–MS). The analytes were extracted from blood by solid-phase extraction (SPE) and derivatized with N -methyl- N -(trimethylsilyl)trifluoroacetamide (MSTFA) with 5% trimethylchlorosilane (TMCS). For all analytes, linearity was observed from 25 (lower limit of quantification, LLOQ) to 800 ng/mL, with coefficients of determination higher than 0.99. The limits of detection (LOD) were 5 ng/mL for α-PVP, 4-Cl-PVP and MDPV and 25 ng/mL for 4-CEC. The method was selective, precise and accurate, and the extraction efficiency was higher than 85% for all analytes. The target cathinones were stable under different stock conditions, being MDPV the most stable and 4-CEC the least stable compound. The validated analytical method was then applied to real samples that previously tested positive for amphetamines, but no positive samples were found for the cathinones under study. The present method describes for the first time the quantification of 4-CEC and 4-Cl-PVP in whole blood samples by GC–MS, allowing their accurate determination in forensic situations where the compounds are involved.